Optimality and stability of intentional and unintentional actions: II. Motor equivalence and structure of variance - Parsa, Behnoosh; Zatsiorsky, Vladimir M.; Latash, Mark L. (Experimental brain research, 2017)
We address the nature of unintentional changes in performance in two papers. This second paper tested hypotheses related to stability of task-specific performance variables estimated using the framework of the uncontrolled manifold (UCM) hypothesis. Our first hypothesis was that selective stability of performance variables would be observed even when the magnitudes of those variables drifted unintentionally because of the lack of visual feedback. Our second hypothesis was that stability of a variable would depend on the number of explicit task constraints. Subjects performed four-finger isometric pressing tasks that required the accurate production of a combination of total moment and total force with natural or modified finger involvement under full visual feedback, which was removed later for some or all of the salient variables. We used inter-trial analysis of variance and drifts in the space of finger forces within the UCM and within the orthogonal to the UCM space. The two variance components were used to estimate a synergy index stabilizing the force/moment combination, while the two drift components were used to estimate motor equivalent and non-motor equivalent force changes, respectively. Without visual feedback, both force and moment drifted toward lower absolute magnitudes. The non-motor equivalent component of motion in the finger force space was larger than the motor equivalent component for variables that stopped receiving visual feedback. In contrast, variables that continued to receive visual feedback showed larger motor equivalent component, compared to non-motor equivalent component, over the same time interval. These data falsified the first hypothesis; indeed, selective stabilization of a variable over the duration of a trial allows expecting comparably large motor equivalent components both with and without visual feedback. Adding a new constraint (presented as a target magnitude of middle finger force) resulted in a drop in the synergy index in support of the second hypothesis. We interpret the force drift as a natural relaxation process toward states with lower potential energy in the physical (physiological) system involved in the task. The results show that presenting sensory feedback on a performance variable makes synergies stabilizing that variable dependent on that particular sensory feedback.